Structural and microbial evidence for different soil carbon sequestration after four-year successive biochar application in two different paddy soils. (September 2020) - Bi, Yucui; Cai, Siyuan; Wang, Yu; Zhao, Xu; Wang, Shenqiang; Xing, Guangxi; Zhu, Zhaoliang
Abstract: Application of biochar (BC) derived from rice straw has generated increasing interest in long-term storage of soil organic carbon (SOC), however its carbon (C) sequestration potential vary widely among agricultural soils despite the same BC dose used. These discrepancies in the ability of soils to sequester C after BC application are poorly understood. Metabolic quotient ( q CO2 ) is a reflection of "microbial efficiency" and linked to SOC turnover across ecosystems. Therefore, we investigated the SOC sequestration and q CO2 in a Yellow River alluvium paddy soil (YP) and a quaternary red clay paddy soil (QP) under rice-wheat annual rotation following 4-year of BC application rate of 11.3 Mg ha −1 per cropping season. BC application consistently brought 65.3 Mg C ha −1 into the soils over 4-year experimental period but increased SOC by 57.6 Mg C ha −1 in YP and 64.5 Mg C ha −1 in QP. Calculating SOC mass balance showed 11.7% of BC-C losses from YP and only 1.16% from QP. BC application stimulated the G + bacterial, fungi, and actinomycetes by increasing O-alkyl C content in YP, while decreased the same microorganisms by decreasing anomeric C–H content in QP. Importantly, higher clay and amorphous Fe (Feo ) contents in QP after BC application protected SOC from further decomposition, which in turn decreased microorganisms and resulted in higher SOC sequestration than YP. Our results indicated that soil properties controlled the extent of SOC sequestration after BC application and site-specific soil properties must be carefully considered to maximize long-term SOC sequestration after BC application. Graphical abstract: Image 1 Highlights: Two paddy soils from northern (YP) and southern (QP) China were used in this study. Biochar (BC) application caused higher SOC sequestration in QP than in YP. BC addition increased OCq and K-strategists in YP due to improved soil condition. BC addition decreased anomeric C and K-strategists in QP due to high Feo content. Site-specific soil properties should take into consideration before BC addition.